Implementation of Service Policy Electronic Identity Card in Humbang Hasundutan District North Sumatera Province - Hutasoit, Imelda; Gaol, Joel Dion Cius Lumban (ARISTO, 2024)
This study aims to analyze the implementation of the Electronic Identity Card (KTP-El) service policy in Humbang Hasundutan Regency, North Sumatra Province. This research is exploratory research with a qualitative approach. Data were collected through interviews, observations, and documentation. Informants were determined by purposive sampling and snowball techniques. The data analysis technique used the Spradley analysis model with four analysis stages: domain, taxonomic, componential, and cultural themes. The results of the study indicate that the implementation of the E-KTP service has not been optimal even though various efforts have been made, it can be seen from the unachieved target for the electronic E-KTP, which is caused by several factors, such as the lack of adequate socialization about the importance of the E-KTP, data recording tools, damaged networks, inadequate staff resources, and low public awareness of the importance of the E-KTP. Efforts that should be made are to conduct education and socialization in more detail and intensive on the significance of E-KTP to the public, repair damaged data recording devices and networks, conduct regular training for unskilled employees in providing E-KTP, clarify SOP regarding the time it takes to record an Electronic Identity Card.